2021
DOI: 10.1097/md.0000000000027012
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the efficacy of Da Vinci robotic or laparoscopic distal subtotal gastrectomy in patients with gastric cancer

Abstract: Background: Robotic-assisted gastrectomy has been used for treating gastric cancer since 2002. This meta-analysis was conducted to systematically evaluate the efficacy of Da Vinci robotic distal subtotal gastrectomy (RDG) or laparoscopic distal subtotal gastrectomy (LDG) in patients with gastric cancer. Methods: We conducted searches in domestic and foreign databases, and collected literature in Chinese and English on the efficacy of RDG and LDG for gastric cancer that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(59 citation statements)
references
References 16 publications
0
43
1
Order By: Relevance
“…Analysis involved all 224 studies: out of them, 193 ones turned as not relevant for title and abstract, while 31 full-texts were considered eligible. Twe of the 31 studies were excluded because they were identified as duplicate publicati After removal of 4 studies not complying with inclusion criteria (1 robotic gastrecto versus open gastrectomy meta-analysis; 1 umbrella review; 1 umbrella review protoc network meta-analysis), 7 meta-analyses underwent qualitative synthesis [14][15][16][17][18][19][20]. No ditional record was found through other source (References list).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis involved all 224 studies: out of them, 193 ones turned as not relevant for title and abstract, while 31 full-texts were considered eligible. Twe of the 31 studies were excluded because they were identified as duplicate publicati After removal of 4 studies not complying with inclusion criteria (1 robotic gastrecto versus open gastrectomy meta-analysis; 1 umbrella review; 1 umbrella review protoc network meta-analysis), 7 meta-analyses underwent qualitative synthesis [14][15][16][17][18][19][20]. No ditional record was found through other source (References list).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Table 1 shows demographic features of 7 included meta-analyses that covered 2000-2020 time frame [14][15][16][17][18][19][20]. Studies included into the meta-analyses ranged from 12 to 40, were almost all retrospective ones and originated from Asian countries (China and Korea, in particular) [14][15][16][17][18][19][20].…”
Section: General Population Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations